PENGARUH BRAND IMAGE DAN PRODUCT DESIGN TERHADAP KEPUTUSAN MENGGUNAKAN BANK DIGITAL (STUDI KASUS BLU BY BCA DIGITAL) - Ahmad, Andita; Mirati, R. Elly; Purwaningrum, Endang (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
Competition in the digital banking market is getting tighter, encouraging digital banking companies to formulate appropriate strategies to be able to compete. This research aims to investigate the influence of brand image and product design on the decision to use a digital bank with a case study of Blu by BCA Digital in Indonesia. Brand image and product design were chosen as the main variables because both have an important role in influencing consumer perceptions and preferences for digital banking services. The research method used was a survey of active Blu by BCA Digital users with a questionnaire as a data collection tool. A total of 100 responses from Blu by BCA Digital users belonging to generation z and millennials in Jabodetabek have been collected using a purposive sampling technique and then analyzed using the multiple regression analysis method with data processing tools, namely SPSS version 26.0. The findings in this research are that brand image and product design partially and simultaneously have a significant positive influence on the decision to use a digital bank with a case study on Blu by BCA Digital. It is hoped that further research can develop by adding other factors to deepen understanding in this context.